Political Corruption and Minority Capture - Pierpaolo Giannoccolo; Maurizio Lisciandra (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This analysis investigates a political corruption model that builds on previous literature on corruption in hierarchies. Our study enriches the literature on political corruption emphasizing the contrasting role of the minorities having a control role of the majorities. In particular, this paper provides a set-up for the conditions in which a briber can choose between either bribing only the majority and accepting the monitoring of the minority, or alternatively, bribing also the minority, which gives up to its control role and increases the probability of success of the illicit action. Minorities can exploit their typical monitoring role in modern democracies either to gain a reputational premium or to get involved in bribing and raising higher stakes. Thus, policy-makers face a sort of paradox when attempting to strengthen the control role of minorities and reduce corrupt behavior because this may cause the opposite effect of inducing the minorities to get involved into the illicit activity and, eventually, spread the corruption disease.
Keywords: D72; D73; K42; 330